Repeatability of Quantitative 18F-FET PET in Glioblastoma. (30th April 2021) - Ferjančič, Peter; Ebert, Martin A; Francis, Roslyn; Nowak, Anna K; Jeraj, Robert
Abstract: Purpose : O-(2-[ 18 F]fluoroethyl)-L-tyrosine (FET), a PET radiotracer of amino acid uptake, has shown potential for diagnosis and treatment planning in patients with glioblastoma (GBM). To improve quantitative assessment of FET PET imaging, we evaluated the repeatability of uptake of this tracer in patients with GBM. Methods : Test-retest FET PET imaging was performed on 8 patients with histologically confirmed GBM, who previously underwent surgical resection of the tumour. Data were acquired according to the protocol of a prospective clinical trial validating FET PET as a clinical tool in GBM. SUVmean, SUVmax and SUV98% metrics were extracted for both test and retest images and used to calculate 95% Bland-Altman limits of agreement (LoA) on lesion-level, as well as on volumes of varying sizes. Impact of healthy brain normalization on repeatability of lesion SUV metrics was evaluated. Results : Tumour LoA were [0.72, 1.46] for SUVmean and SUVtotal, [0.79, 1.23] for SUVmax, and [0.80, 1.18] for SUV98% . Healthy brain LoA were [0.80, 1.25] for SUVmean, [0.80, 1.25] for SUVmax, and [0.81, 1.23] for SUV98% . Voxel-level SUV LoA were [0.76, 1.32] for tumour volumes and [0.80, 1.25] for healthy brain. When sampled over maximum volume, SUV LoA were [0.90, 1.12] for tumour and [0.92, 1.08] for healthy brain. Normalization of uptake using healthy brain volumes was found to improve repeatability, but not after normalization volume size of about 15 cm 3 . Conclusions Advances in Knowledge and Implications for Patient Care : Repeatability of FET PET is comparable to existing tracers such as FDG and FLT. Healthy brain uptake is slightly more repeatable than uptake of tumour volumes. Repeatability was found to increase with sampled volume. SUV normalization between scans using healthy brain uptake should be performed using volumes at least 15 cm 3 in size to ensure best imaging repeatability.